Association between the serum alpha-1-acid glycoprotein concentrations and depression in US adult women: a cross-sectional study - Yuanyuan Zhong; Chunyue Fang; Tianliang Yao; Hongjin Wang; Min Jiang (BMC Psychiatry)
Abstract Background Emerging evidence has demonstrated a positive association of inflammation with depression. As an acute-phase reactant predominantly synthesized in hepatocytes, alpha-1-acid glycoprotein (AGP) serves as a sensitive biomarker of inflammation. However, there is a limited study to explore the relationship between AGP and depression. Currently, the association of AGP with depression is controversial. Methods This study utilized data from the National Health and Nutrition Examination Survey (NHANES) collected between 2021 and 2023. The Patient Health Questionnaire-9 (PHQ-9) was employed to assess depressive symptoms, with a score ≥ 10 indicating clinically relevant depression. We utilized weighted multivariate logistic regression for depression outcomes, weighted linear regression for continuous PHQ-9 scores, and restricted cubic splines (RCS) to examine potential nonlinear relationships between AGP and depression. To evaluate the robustness of these associations, we conducted comprehensive subgroup analyses with interaction tests and multiple sensitivity analyses. Results Serum AGP concentrations exhibited a significant positive association with depression among U.S. adult women, demonstrating a linear dose-response relationship. In the fully adjusted model, each ln-unit increase in AGP concentrations was associated with a 1.13-fold higher odds ratio of depression (OR: 2.13, 95% CI: 1.26–3.64) and a 1.47-point elevation in PHQ-9 values (β: 1.47, 95% CI: 0.37–2.56). Moreover, participants in the highest AGP quartile had a 0.72-fold increased odds ratio of depression (OR: 1.72, 95% CI: 1.03–2.87) and a 1.32-point higher PHQ-9 score (β:1.32, 95% CI: 0.31–2.34) compared to those in the lowest quartile. This positive association remained consistent across multiple subgroup analyses. Conclusions Serum AGP concentrations demonstrated a significant positive linear association with depressive symptoms among nationally representative samples of U.S. adult women.